THE EFFECT OF ANKYLOSING SPONDYLITIS ON HEALTH-RELATED QUALITY OF LIFE AND DIFFERENT ASPECTS OF SOCIAL LIFE - Ahmet Özgül,; Fatma Peker,; M. Ali Taşkaynatan,; A. Kenan Tan,; Kemal Dinçer,; T. Alp Kalyon, (Archives of Rheumatology, 2003)
The aim of this study is to put forward the patients' assessment about the disease, impact of the disease on whole life fields, and to measure of quality of life in ankylosing spondylitis. 101 patients with the diagnosis of AS according to modified New York criteria were enrolled in this study. The patients' general assessment about the disease was assessed with Likert scale, and quality of life was assessed with short form (SF-36). The most affected subscales of quality of life were role limitations caused by physical health problems, general health perceptions and pain. The physical functioning and social functioning value differences between employed and unemployed patients before the disease were statistically significant (p<0.004). The physical functioning, role limitations caused by physical health and emotional problems, general health perception, vitality, social functioning and mental health value differences between the patients employed before the disease but unemployed after the disease and employed before and after the disease were statistically different (p<0,001, p<0,001, p=0,007, p=0,001, p=0,001, p<0,001 and p=0,005 respectively). The physical functioning and general health value differences between the patients unemployed and employed before but unemployed after the disease were statistically significant (p=0.002 and p=0.002 respectively). The values of subscales were lower in the patients unemployed because of the disease. General health and physical role power values of patients with an education duration below and over 8 years were significantly different (p=0.002 and p=0.013 respectively). The difference in approach to marriage between the patients according to education level was also found to be significant (p=0.024). As a result ankylosing spondylitis is such a chronic disesase in which the life fields and quality of life are affected in addition to physical harm.